Prognostic factors of survival after neoadjuvant treatment and resection for initially unresectable pancreatic cancer - Klaiber, Ulla; Schnaidt, Eva Simone; Hinz, Ulf; Gaida, Matthias; Heger, Ulrike; Hank, Thomas; Strobel, Oliver; Neoptolemos, John P.; Mihaljevic, André Leopold; Büchler, Markus W.; Hackert, Thilo (Annals of surgery, 2019)
Mini - We analyzed prognostic factors after neoadjuvant therapy and resection in 280 patients with initially unresectable pancreatic cancer—the largest single-center study reported. We found that preoperative CA 19-9 levels, lymph node status, presence of distant metastases, and vascular involvement were all independent overall survival predictors, but not resection margin status. - Objective: - To evaluate the impact of clinical and pathological parameters, including resection margin (R) status, on survival in patients undergoing pancreatic surgery after neoadjuvant treatment for initially unresectable pancreatic ductal adenocarcinoma (PDAC). - Background: - Prognostic factors are well documented for patients with resectable PDAC, but have not been described in detail for patients with initially unresectable PDAC undergoing resection after neoadjuvant therapy. - Methods: - Prospectively collected data of consecutive patients with initially unresectable pancreatic cancer treated by neoadjuvant treatment and resection were analyzed. The R status was categorized as R0 (tumor-free margin >1 mm), R1 ≤1 mm (tumor-free margin ≤1 mm), and R1 direct (microscopic tumor infiltration at margin). Clinicopathological characteristics and outcomes were compared among these groups and tested for survival prediction. - Results: - Between January, 2006 and February, 2017, 280 patients with borderline resectable (n = 18), locally advanced (n = 190), or oligometastatic (n = 72) disease underwent tumor resection after neoadjuvant treatment. Median overall survival from the time of surgery was 25.1 months for R0 (n = 82), 15.3 months for R1 ≤1 mm (n = 99), and 16.1 months for R1 direct (n = 99), with 3-year overall survival rates of 35.0%, 20.7%, and 18.5%, respectively (P = 0.0076). The median duration of the neoadjuvant treatment period was 5.1 months. In multivariable analysis, preoperative CA 19-9 levels, lymph node status, metastasis category, and vascular involvement were all significant prognostic factors for overall survival. The R status was not an independent prognostic factor. - Conclusions: - In patients undergoing resection after neoadjuvant therapy for initially unresectable PDAC, preoperative CA 19-9 levels, lymph node involvement, metastasis category, and vascular involvement, but not the R status, were independent prognostic factors of overall survival.